Bilateral Pneumothorax After Minimally Invasive Repair of Pectus Excavatum: Report of a Rare Life-Threatening Complication - Agamennone, Marco; Lena, Federica; Donati, Francesco; Calevo, Maria Grazia; Guerriero, Vittorio; Torre, Michele (The Thoracic and Cardiovascular Surgeon, 2025)
Minimally invasive repair of pectus excavatum (MIRPE) creates an iatrogenic communication between the pleural cavities, known as a “buffalo chest.” Patients with pectus excavatum are also at increased risk of spontaneous pneumothorax due to congenital apical blebs. When these two conditions coexist, the risk of bilateral spontaneous pneumothorax becomes potentially life-threatening. This study aims to evaluate the incidence and characteristics of spontaneous pneumothorax following MIRPE, with particular attention to the presence and role of congenital blebs.We retrospectively reviewed patients who underwent MIRPE between 2005 and 2024 to identify cases of spontaneous pneumothorax. Only cases occurring at least 1 month postoperatively and unrelated to intraoperative thoracoscopy were included. Patients were followed for at least 10 months. We analyzed laterality, clinical presentation, presence of blebs, treatment, and outcomes. A systematic literature review was also conducted to explore the relationship between buffalo chest, pneumothorax, and pectus excavatum.Among 795 patients, 7 developed spontaneous pneumothorax: 4 unilateral, 3 bilateral. In six cases, blebs were identified and treated with thoracoscopic bullectomy and pleurodesis. Two patients with bilateral pneumothorax experienced cardiac arrest: one recovered after emergency drainage; the other died in a peripheral hospital, where blebs were suspected but not confirmed. The literature review identified nine similar cases in five reports.Bilateral spontaneous pneumothorax after MIRPE can be a life-threatening emergency due to the buffalo chest. Patients and families should be informed of this rare but serious risk to enable early recognition and prompt treatment. Preoperative detection of apical blebs may help reduce this risk.
Keywords: pectus excavatum; carinatum; pneumothorax; pleural disease (incl. drainage); chest wall; minimally invasive surgery (includes port access minithoracotomy); pediatric